Character of Traditional Street: An Overview of Physical Components Associated with Building, Landscape and Street Pattern in Royal Town - Wan Norisma Wan Ismail; Ja'Afar N.H.; Fadli Arabi; Elina Mohd Husini (Institute of Physics Publishing, 2024)
Indexed by Scopus